The Correlation Between Maternal Hemoglobin Concentration And Neonatal Birth Weigth In Kirana Maternal Hospital - Ni Nyoman Yeyen Abriyani (Universitas 'Aisyiyah Yogyakarta, 2020)
World Health Organization (2014) data shows that Maternal Mortality Rate in the world reached 289,000 inhabitants. Indonesian Demographic Health Survey in 2012 mentioned that the maternal mortality rate (MMR) in Indonesia reached 359 / 100,000 live birth. Low hemoglobin levels in pregnant women can cause anemia. It can also increase the frequency of complications in pregnancy and childbirth as well as increase the risk of maternal mortality, the rate of prematurity, low birth weight. This study aims to determine the correlation between hemoglobin levels of pregnant women and birth weight at Kirana Maternal Hospital. This study applied a correlational study using cross sectional design. The data types used This study applied a correlational study using cross sectional design. The data types used secondary data obtained from medical records and maternal health book. The results of the study later in the normality test and analyzed using Pearson test. The results showed that there was no study later in the normality test and analyzed using Pearson test. The results showed that there was no significant correlation between hemoglobin levels of pregnant women and birth weight in Kirana Maternal Hospital in 2016 with 0.00 significance value 0.05